Avaliação da resistência à corrosão dos aços inoxidáveis duplex ASTM A890/A 890M grau 3A e 1B - Forte, Ana Caroline Ferreira (2014)
Duplex stainless steels are used in wide scale for the manufacture of cast components of centr ifugal pumps that are applied in offshore platforms. The operations in a platform may take place in the range of 300 to 500 °C, wherein the precipitation of harmful phases is possible, being one of them the line alfa phase ( α ’) that it has its accentuated precipitation the temperature of 475 ° C . This phase causes a sudden reduction in corrosion resistance and mechanical properties of the material. Therefore, in the presente work the susceptibility to corrosion of cast duplex s tainless steels ASTM A890/A 890M Grade 3A and grade 1B was evaluated after different aging times at 475° C, making a comparison between two steel due to the presence of copper as an alloying element added to steel of grade 1B. The specimens tested passed t hrough heat treatment at a temperature of 475° C for times of 2, 10, 50 and 100 hours followed by a water quenching. The microstructural characterization and the Brinell hardness test were carried out in the treated specimens. The electrochemical tests per formed were the monitoring of the open circuit potential; Anodic potentiodynamic polarization; cyclic potentiodynamic polarization; electrochemical impedance spectroscopy using an electrolyte of NaCl 0.68 mol/dm 3 in order to simulate a concentration close to seawater. The critical pitting temperature was determined using an electrolyte NaCl 1 M according to the standard ASTM G150 - 13. In the characterizations microstructural it was observed the structure of two - phase materials consisting of a ferritic matrix with islands of austenite in equivalent proportions. The hardness tests had shown gradual increase of the hardness of the material with the increase of the treatment time for both steels. The electrochemical tests indicated that, for the studied steel 1B, the sample that underwent heat treatment for 50 h presented a greater corrosion resistance and a higher critical pitting temperature, already for the steel 3A, the sample heat treated for 100h showed better results of corrosion resistance and higher criti cal pitting temperature.